Kajian Keberlajutan Pengelolaan Lingkungan Kawasan Industri Studi Kasus di Kawasan Industri Jababeka Bekasi - Temmy Wikaningrum (Journal of Environmental Engineering and Waste Management, 2016)
Industrial Estate development has an important role for national economic growth. The government regulation number 24 year 2009 (replaced by number 142 year 2015) states that most of all industrial / manufacturing activities in Indonesia should be located in industrial estate. By this reason, an integrated environmental management in industrial estate will become the significant strategic to support national sustainable development. Industrial estate developer should have a proper environmental management system to minimize the negative impacts of its activities to environment. The sustainability performance analysis was conducted in Jababeka Industrial Estate, year 2008-2014, which refer to PROPER KLHK green rating criterias (the assessment program for company performance rating in environmental management issued by Ministry of Environment and Forestry). The analysis was approached by multi-dimensional scaling (MDS) with rapfish software modification. The sustainability analysis result showed that the ‘sustainable’ status was only achieved on institutional management dimension (Stress: 23.15%, R2: 94.4), while other dimensions (ecology, technology, social and economy) had the status of ‘less sustainable’ or ‘not sustainable’. The dominant leverage factors in environmental management were 3R hazardous waste implementation (RMS 8.69 > median 4.35), the financing of water conservation and wastewater reduction (RMS 4.08 > median 2.275), community development implementation (RMS 6.38 > median 5.69), air emission reduction technology (RMS 10.65 > median 2.79), and benchmarking policies (RMS 15.45 > median 12.15). By considering this dominant leverage factors, Industrial Estate Company was recommended to apply the strategic plans to achieve the sustainable performance in the near future.